2017
DOI: 10.1002/ajh.24974
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of quizartinib in combination with induction and consolidation chemotherapy in patients with newly diagnosed acute myeloid leukemia

Abstract: Novel therapies have potential to improve outcomes in patients with acute myeloid leukemia (AML) harboring FLT3-ITD mutations that have high risk of relapse and poor survival following standard of care (SOC) cytarabine/anthracycline-based induction/consolidation chemotherapy.Quizartinib is a selective and highly potent FLT3 inhibitor that has shown strong single-agent activity in relapsed or refractory (R/R) AML. This phase 1, open-label, sequential group dose-escalation trial (NCT 01390337) is the first evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 35 publications
5
55
0
1
Order By: Relevance
“…It is also plausible that the addition of FLT3 inhibitors to induction and/or consolidation therapy prior to stem cell transplantation will yield a potential benefit of reducing early relapses and increasing the likelihood of proceeding with HSCT. Recent studies with improved CR rates and prolonged CR duration when FLT3 inhibitors are used in combination with hypomethylating agents(35) or chemotherapy(40–42) is promising that more patients can be brought to allogeneic HSCT without early relapse while logistics of allogeneic HSCT like donor identification process is ongoing. We believe that it is worth investigating the feasibility of using new generation FLT3 inhibitors incorporated into leukemia treatment before HSCT, to conditioning regimen as a part of HSCT and then in post-transplant maintenance after HSCT, in FLT3-ITD mut patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that the addition of FLT3 inhibitors to induction and/or consolidation therapy prior to stem cell transplantation will yield a potential benefit of reducing early relapses and increasing the likelihood of proceeding with HSCT. Recent studies with improved CR rates and prolonged CR duration when FLT3 inhibitors are used in combination with hypomethylating agents(35) or chemotherapy(40–42) is promising that more patients can be brought to allogeneic HSCT without early relapse while logistics of allogeneic HSCT like donor identification process is ongoing. We believe that it is worth investigating the feasibility of using new generation FLT3 inhibitors incorporated into leukemia treatment before HSCT, to conditioning regimen as a part of HSCT and then in post-transplant maintenance after HSCT, in FLT3-ITD mut patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase 1 dose escalation study of quizartinib with induction chemotherapy, 40 mg per day of quizartinib given on days 4-17 with standard 7+3 induction chemotherapy was identified as the maximal tolerated dose. 76 Preliminary efficacy from the trial showed a 74% (14/19) CRc, and the phase 3 randomized QuANTUM-First trial is ongoing to evaluate efficacy. 77 The results of induction chemotherapy trials with more potent second-generation FLT3 inhibitors such as quizartinib will be interesting to compare with results from the midostaurin RATIFY trial since many have speculated that some of midostaurin's clinical success is partly attributable to off-target effects.…”
Section: Future Directionsmentioning
confidence: 99%
“…In an attempt to improve the response rate and more importantly the duration of response AC220 has been combined with intensive chemotherapy (anthracycline and cytarabine in the “3+7” regimen) in patients ages 18–60 years(77). Initial data from this study demonstrated that quizartinib could be safely administered with induction or consolidation chemotherapy in younger AML patients.…”
Section: Molecular and Multikinase Inhibitor Therapies In The Fromentioning
confidence: 99%